Endovascular Repair (EVAR) Better Than Open Surgical Repair (OSR) in Abdominal Aortic Aneurysm: A Systematic Review - M. Iqbal Rifai Fauzi; Karina Asysyifaa Alemina Ramadhani Ginting (Buletin Farmatera, 2023)
Abstract: Adult mortality from rupture of an abdominal aortic aneurysm (AAA) is significant. Patients are offered either open surgery surgery (OSR) or endovascular repair (EVAR). EVAR has been a choice for AAA treatment. However, EVAR has more post-procedural complications than OSR. This study examines current evidence contrasting the intricacy of EVAR and OSR as medical procedure choices for stomach aortic aneurysms (AAA). The published research article was searched in PubMed, Science Direct, BMJ, and Google Scholar databases with the keywords AAA, EVAR, OSR, and complication. This systematic review was written based on Prisma guidelines. The inclusion criteria for this study are as follows: research is conducted within the past five years, and the outcome should compare the complication of EVAR and OSR. The result of the selection found 9 articles that were included in the inclusion criteria. A total of 67.114 patients with all types of AAA and all types of ages were included in this study. OSR has a higher mortality rate than EVAR, however, OSR reintervention rate was lower. This study found the EVAR procedure (73%) more popular than OSR (27%). Many studies revealed EVAR had high rates of reinterventions mainly due to endograft-related complications. Our review was also in line with this statement. In conclusion, EVAR is better for AAA treatment, however, EVAR had a high reintervention rate.